CORPORATE CONSOLIDATION PECULIARITIES IN UKRAINIAN RETAIL GROCERY MARKET - Iryna Sevruk (European Scientific Journal, ESJ, 2014)
The purpose of the article is to study the state and general retail trade development trends in Ukraine, monitor processes of consolidation and concentration of market power in Ukrainian grocery market, evaluate concentration levels of international trade FMCG companies and analyze the impact of the mentioned processes on the competitive environment of the domestic retail turnover. Analysis and systematization of scientific research of foreign and Ukrainian scientists allowed choosing concentration ratios for different quantity of firms and Herfindahl-Hirschman index as methodological tools for a study of the market concentration level and accumulation of assets, consolidation of market power by the international FMCG companies in the retail market in Ukraine. The Ukrainian grocery market is defined to have certain specific features which despite the overall positive evolution of retail trade volume and retail trade chains turnover are reflected in the dominance of local business representatives on it, low concentration level versus other European countries, as well as negative concentration dynamics of international capital in the retail grocery market in Ukraine.